Legal Risk Transformation: Loss of Creditors' Enforcement Rights of Third-Party Fiduciary Guarantees Objects Due to Lack of Registration - Sulastri, Sulastri; Nugroho, Andrianto Adhi; Surahmad, Surahmad (Bacarita Law Journal, 2025)
This study analyzes the shift in legal risk resulting from negligence in registering fiduciary guarantees and the superiority of protection for bona fide third parties. The primary objective is to examine how a creditor's failure to register a fiduciary guarantee transforms property rights into personal claims against the debtor, as well as to analyze how the protective principle of Article 1977 of the Civil Code nullifies the creditor's right of execution under a fiduciary guarantee deed. The research method used is normative legal analysis, employing a literature review approach to examine relevant legislation, legal doctrine, and case law pertaining to fiduciary collateral, property law, and third-party protection. Primary and secondary data are analyzed qualitatively to construct a coherent legal argument. The research findings indicate that the registration of fiduciary collateral is crucial in creating in rem property rights, providing executory power and enforceability against third parties. Failure to register results in the degradation of the creditor's rights to mere personal claims, which are vulnerable to legal risks. Furthermore, the existence of Article 1977 of the Civil Code effectively protects bona fide third parties who acquire movable property subject to fiduciary collateral. This protection nullifies the creditor's right to execute on the property, forcing the creditor to seek only personal compensation from the debtor. This underscores that without valid registration, creditors face significant risks, highlighting the importance of compliance with registration procedures for legal certainty